Contextualization of Suluk Candra’s Character Values - Moch Lukluil Maknun; Umi Muzayanah (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
Indonesia's education is heavily focusing on developing students' good characters. Character values can be explored from the legacy of the previous generations through old scriptures. Of many genres of Javanese scriptures containing character values are the wulang scripts, such as Suluk Candra, written by Prince Wijil Kadilangu  and stored  in  Museum Rekso Pustaka Mangkunegaran Library. This article explores the character values depicted by  the  manuscript  and  contextualizes  them  with  today's  education.  The present study employs the principles of philology and the interpretation of texts. The working principle of philology aims to produce a text edition, while interpretation aims to analyze the content of the text. It is found that Suluk Candra is a script containing Islamic values, teaching at least four ethics that can be contextualized with the world of education in the current 4.0 era. On the ethical values, there are ethics to the king/ leader/ state, ethics to teachers, ethics to fellow human beings, and ethics to oneself. Besides, there are also values of character education in Suluk Candra. Those character values are relevant to the present day, including the love of science, logical thinking, critical, creativity, innovation, religiosity, honesty, and nationalism.